The Competence Readiness of the Electrical Engineering Vocational High School Teachers in Manado towards the ASEAN Economic Community Blueprint in 2025 - Fid Jantje Tasiam; Djoko Kustono; Purnomo Purnomo; Hakkun Elmunsyah (Intelektual Pustaka Media Utama, 2017)
This paper presents the competence readiness of the electrical engineering vocational high school teachers in Manado towards ASEAN Economic Community blueprint in 2025. The objective of this study is to get the competencies readiness description of the electrical engineering vocational high school teachers in Manado towards ASEAN Economic Community blueprint in 2025. Method used quantitative and qualitative approach which the statistical analysis in quantitative and the inductive analysis used in qualitative. There were 46 teachers of the electrical engineering vocational high school in Manado observed. The results have shown that the competencies readiness of the electrical engineering vocational high school teachers in Manado such as: pedagogical, professional, personality, and social were 13.04%, 19.56%, 19.56%, and 19.56% respectively. The results were still far from the focus of the ASEAN economic community blueprint in 2025, so they need to be improved through in-house training, internship programs, school partnerships, distance learning, tiered training and special training, short courses in educational institutions, internal coaching by schools, discussion of educational issues, workshops, research and community service, textbook writing, learning media making, and the creation of technology and art.